The Effect of Price and Product Quality toward Brand Switching through Consumer Satisfaction (Study on Local Skincare Product Users Who Switched to Korean Skincare Products) - Gaffar, Novia Ramadhani; R. Yuniardi Rusdianto (BASKARA : Journal of Business and Entrepreneurship, 2025)
This study aims to analyze the effect of price and product quality on brand switching decisions, with customer satisfaction as an intervening variable among users of local skincare who switch to Korean skincare. This research employs a quantitative approach, with data collected through questionnaires. The sampling technique used is purposive sampling, with 205 respondents. The sample criteria include Generation Z residing in Surabaya, aged 13 years, and having experience using local and Korean skincare products at least once. Data analysis in this study was conducted using SmartPLS 4.0. The findings indicate that price and product quality significantly influence customer satisfaction. Additionally, customer satisfaction has a significant effect on brand-switching decisions. However, the results reveal that price does not directly influence brand-switching decisions, whereas product quality significantly impacts consumers' decisions to switch brands. Furthermore, customer satisfaction is a mediating variable in the relationship between price and product quality with brand switching decisions. These findings suggest that while product price shapes customer satisfaction, product quality has a greater influence on consumers' decisions to switch brands.